Trend, factors and consequences of overweight and obesity in the Malaysian Army / Azizan Omar - Azizan, Omar (2019)
The prevalence of overweight and obesity has been on the rise since decades affecting all nations across the world in both the general population and military organisation. The objectives of this study were to determine the trend and prevalence of overweight and obesity, factors associated with it, and their consequences on sickness absenteeism and physical fitness in the Malaysian Army. This study was divided into two phases. Phase 1 was a retrospective cohort study involving extraction of secondary data from 2275 army personnel medical and service records. Socio-demographic and occupational information was gathered from the service record, while information on Body Mass Index (BMI) and sickness absenteeism were extracted from the medical record. Phase 2 was a cross-sectional study involving 836 personnel. Phase 2 involved anthropometric measurement, body composition analysis, and Basic Military Fitness Test (BFMT), as well as questionnaires on smoking, physical activity (IPAQ) and dietary intake (24-hour dietary recall). The trend of overweight and obesity in the Malaysian Army has been increasing from 1990 to 2015. In 2015, the prevalence of overweight and obesity was 34.0% and 7.7% respectively. BMI had a high sensitivity but low specificity in classifying overweight especially in males. Around 62% of overweight males had a normal body fat percentage (BF%). Univariately, increasing age and duration of service, married, senior rank, household income >RM3000, and less frequent intake of food from home and high energy intake were associated with overweight and obesity. However, in the multivariate analysis, only the duration of service was significant. Compared to those who had served less than 5 years, the odds of being overweight and obese among those who had served between 5 to 10 years, iv between 10 to 15 years, and more than 15 years were 5.45 (95% CI: 1.71,8.30), 5.70 (95% CI: 1.44,12.64), and 9.87 (95% CI: 1.12,17.00) respectively. Overweight and obesity, increasing age, and females were significantly associated with higher sickness absenteeism and presenteeism. Overweight and obesity were also significantly associated with failing the BMFT. Compared to the normal weight personnel, the odds of failing the BMFT among the overweight and obese personnel were 1.60 (95% CI: 1.07, 2.39) and 2.11 (95% CI: 1.01, 4.43) respectively. The increasing trend of overweight and obesity, together with their consequences on productivity and performance should be concerning to the Malaysian Army. Intervention and preventive measures should start early in their career before they reached the overweight status. BF% should be used together with BMI to give more accurate classification of obesity and to avoid discriminating overweight personnel with high lean muscle mass. BFMT should be incorporated in the overall assessment together with BMI and BF% to ensure that the personnel are serious about maintaining their health and fitness.